I Can't Call Australia Home: Finding My Father in the Archives. Issue 4 (2nd October 2017) - O'Neill, Betty Maria
ABSTRACT: Through a hybrid memoir and non-fiction writing format, this essay explores the research and reconstruction of my father's life: a patremoir project examining an encounter with a rescued family archive that revealed my father's secret other life and a longing for 'home' unquenched by immigrant life in the 'land of opportunities'. After twenty years of living in Australia, my Polish father, Antoni Jagielski, a WWII concentration camp survivor, decided to return 'home' to Poland, to his culture and to his other family. This work uses the lens of my father's story and mine, to examine fractured families, separation, displacement, the transmission of intergenerational memory and the transnational history of post-1945 Australia. My research intervention, a field trip to Poland in 2013, unexpectedly uncovered a family archive consisting of letters, postcards, official documents and certificates, photos and material artefacts. Additional information about my father's life has been gathered from archives in Auschwitz, Mauthausen/Gusen, the Polish Underground Movement Study Trust and the Polish Institute in London. This diversity of sources, typical for scholars in this part of the world researching immigrant family stories, has provided the fragments to make meaning of a life and the difficulties of post-war immigration to Australia.